DISEMINASI PENERAPAN TEKNOLOGI AUDIO ON DEMAND MELALUI PODCAST SEBAGAI MEDIA INFORMASI DI ERA INDUSTRI 4.0 - Halil Akhyar; Deasy Mariyani; Susi Rahayu; Muhamad Ali (Universitas Mataram, 2022)
Information technology is a technology utilized to create, modify, communicate or disseminate up-to-date information through an advanced media. Podcast is the current channel to spread out an informative and educational information. The popularity of podcasts as a public medium to deliver information increases significantly in the recent year. This is supported by the condition of the Covid-19 pandemic. The podcast is continuously applicated in all areas, such as entertainments, governments and educational circumstances. The two-way communication has become an interactive broadcasting system not only for the young people but also for the elderly people. So that the presence of podcasts continues to be positively welcomed by the community. The event aims to form a podcast as a media for promotion and dissemination of information related to research and service innovations produced by lecturers at the University of Mataram. It is carried out in some stages, including surveying the situation and field conditions, implementating, and evaluating. In terms of the implementation phase, it is divided into three main activities, such as socializing, training, and mentoring. To facilitate these activities, several approaches were applied, like participatory rural appraisal (PRA), persuasive approaches, and educational approaches. The results of the survey conducted by the health promotion team from the health department of West Nusa Tenggara Province showed that LPPM required several equipment, such as cameras/webcams, microphones, earphones, a mixer, tripods, lightings, an OBS software, an Adobe Premier Pro, and a personal computer. In addition, from the results of observations, it is concluded that the Research and Service Institute (LPPM) of the Mataram University has a suitable room to hold the podcast. Overall, the implementation of podcast at the LPPM has been successfully implemented. The evaluation as one of the most important part shows that there are technical and non-technical obstacles occurred, such as none-standardized computer equipment and room arrangements. This is an important note for the next implementation. However, in general, the podcast as an informative, educative, and accurate information and promotion media has been successfully established at the LPPM of Mataram University.